Cloning and Sequencing of a Genomic Island Found in the Brazilian Purpuric Fever Clone of Haemophilus influenzae Biogroup Aegyptius - McGillivary, Glen (American Society for Microbiology, 2005)
A genomic island was identified in the Haemophilus influenzae biogroup aegyptius Brazilian purpuric fever (BPF) strain F3031. This island, which was also found in other BPF isolates, could not be detected in non-BPF biogroup aegyptius strains or in nontypeable or typeable H. influenzae strains, with the exception of a region present in the type b Eagan strain. This 34,378-bp island is inserted, in reference to H. influenzae Rd KW20, within a choline transport gene and contains a mosaic structure of Mu-like prophage genes, several hypothetical genes, and genes potentially encoding an Erwinia carotovora carotovoricin Er-like bacteriocin. The product of the tail fiber ORF in the bacteriocin-like region shows a hybrid structure where the C terminus is similar to an H. influenzae phage HP1 tail protein implicating this open reading frame in altering host specificity for a putative bacteriocin. Significant synteny is seen in the entire genomic island with genomic regions from Salmonella enterica subsp. enterica serovar Typhi CT18, Photorhabdus luminescens subsp. laumondii TT01, Chromobacterium violaceum, and to a lesser extent Haemophilus ducreyi 35000HP. In a previous work, we isolated several BPF-specific DNA fragments through a genome subtraction procedure, and we have found that a majority of these fragments map to this locus. In addition, several subtracted fragments generated from an independent laboratory by using different but related strains also map to this island. These findings underscore the importance of this BPF-specific chromosomal region in explaining some of the genomic differences between highly invasive BPF strains and non-BPF isolates of biogroup aegyptius.